Upaya Meningkatkan Kemampuan Membaca Al Quran Dengan Pelatihan Tartil Irama Jiharkah di Madin Az Zahro Desa Prajegan Kecamatan Sukorejo Ponorogo - Taufik Yunarta; Kunti Nadiyah Salma; Muhamad Asvin Abdur Rohman (Social Science Academic, 2025)
The Koran is the holy book of Muslims and a guide for humans. Every Muslim is required to study and understand the contents of the Koran. Learning to read the Koran requires paying attention to tartil. Tartil is the ability to read the Koran slowly by paying attention to the correct pronunciation and recitation. So we held tartil maqom Jiharkah training for the children of Madrasah Diniyah Az Zahro, Prajegan Village. Through this Tartil Maqom Jiharkah training, it is hoped that children can read the Al-Quran well and enjoy it. The children were very enthusiastic about learning the tartil rhythm of this jiharkah. At the end of the Jiharkah rhythm trail training, the children who participated in the Jiharkah rhythm training were publicly displayed. Moreover, the results of this performance show that the participant's ability to read the Koran increased after participating in Tartil Tartil Irama Jiharkah.